Preparation and activity evaluation of angiotensin-I converting enzyme inhibitory peptides from protein hydrolysate of mulberry leaf - Chen, Yu; Zhang, Yu; Qi, Qianhui; Liang, Feng; Wang, Nan; Chen, Qihe; Li, Xue; Sun, Suling; Wang, Xinquan; Bai, Kaiwen; Wang, Wei; Jiao, Yingchun (Frontiers in Nutrition, 2023)
Angiotensin-I converting enzyme (ACE) inhibitory peptides drew wide attention in the food industry because of their natural reliability, non-toxicity, and safety. However, the characteristics of ACE inhibitory peptides obtained from protein hydrolysate of mulberry leaf prepared by Flavourzyme were still unclear. Based on the single-factor test, the Plackett-Burman test and response surface test were used to determine the key factors affecting the ACE inhibition rate in mulberry leaf protein hydrolysate and the optimum conditions of enzymatic hydrolysis. The results showed that the optimum technical parameters were as follows: the ratio of material to liquid is 1: 25 (w / v，g/mL), the Flavourzyme to substrate ratio was 3,000 U/g, the temperature of enzymatic hydrolysis was 50 ℃, pH was 6.3, and the time of enzymatic hydrolysis was 2.9 h. The ACE inhibitory peptides in the mulberry leaf protein hydrolysates were purified by ultrafiltration and gel filtration, aiming to obtain the highest active component. The 12 peptide sequences were identified by reverse liquid chromatography-mass spectrometry, and then, they were docked to the crystal structure of human angiotensin-Ⅰ converting enzyme (1O8A), and the interaction mechanisms of 12 peptide sequences and 1O8A were analyzed. The docking results showed that among the 12 peptide sequences, ERFNVE (792.37 Da), TELVLK (351.72 Da), MELVLK (366.72 Da), and FDDKLD (376.67 Da), all had the lowest docking energy, and inhibition constant. The chemosynthetic ERFNVE (IC50:2.65 μg/mL), TELVLK (IC50:0.98 μg/mL), MELVLK (IC50:1.90 μg/mL) and FDDKLD (IC50:0.70 μg/mL) demonstrated high ACE-inhibitory activity with competitive inhibition mode. These results indicated that the ACE-inhibiting peptides from mulberry leaf protein hydrolyzed (FHMP) had the potential activities to inhibit ACE and could be used as functional food or drugs to inhibit ACE. This work provides positive support for mining the biological activity of mulberry leaves in the treatment of hypertension.